2019
DOI: 10.21744/irjmis.v6n3.634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emotional and spiritual intelligence on transformational leadership and impact on employee performance

Abstract: The population of this research is all operator employees of PT. Gas Station Pratama Anugrah Dewata who is an employee with contract status. The sampling technique used in this study is saturated sampling or census with the research instrument using a questionnaire. Because the population is relatively small, all populations are used as samples, so the number of samples in this study were 40 operator employees of PT Gas Station Pratama Anugrah Dewata. Data were then analyzed using path analysis and Sobel test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
(19 reference statements)
1
20
1
1
Order By: Relevance
“…Self-awareness about God's command will develop positive emotional and rational thinking ability in facing any problem and finally improve our action to be more positive as a proof of our faith and gratitude to the Creator [29,30]. Hence, developing leadership skills by integrating spiritual awareness will foster a high sense of responsibility [28,31].…”
Section: Resultsmentioning
confidence: 99%
“…Self-awareness about God's command will develop positive emotional and rational thinking ability in facing any problem and finally improve our action to be more positive as a proof of our faith and gratitude to the Creator [29,30]. Hence, developing leadership skills by integrating spiritual awareness will foster a high sense of responsibility [28,31].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results indicated that spiritual intelligence adds to the success of new products in a positive manner. e previous studies [56] also comment in this favor for they examine that the incorporation of spiritual intelligence in organizational individuals increases the market for the new products by creating confidence in the customers. Finally, the results have indicated that the innovation of new products has a considerable moderating role between nonartificial intelligence like emotional intelligence and spiritual intelligence and new product success.…”
Section: Discussionmentioning
confidence: 99%
“…Several other researchers have found that emotional intelligence affects employee performance. The better a person's performance, the better their emotional intelligence (Harahap & Sagala, 2019;Mamangkey et al, 2018;Mulyasari, 2018;Nugraha, 2019), other studies have found other things that can affect emotional intelligence including social interaction (Damayanti, Putri, & Wardani, 2014;Sahputra & Hayati, 2019), coping strategies can also affect the emotional intelligence of working students (Felix et al, 2019), work that puts excessive pressure also affects emotional intelligence (Farrastama & Asmony, 2019), expressing thoughts through writing can affect emotional intelligence (Kirk et al, 2011), and leadership can affect emotional intelligence (Allameh & Khazaei, 2015;Krisnanda et al, 2019;Suryana, 2019). The previous studies on emotional intelligence are mostly applied in the work field, but in this study, it is applied in education.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have examined emotional intelligence including: analyzing the relationship of emotional intelligence and employee performance (Brunetto, Teo, Shacklock, & Farr-wharton, 2012;Cartwright & Pappas, 2008;Farrastama & Asmony, 2019;Feyerhem & Rice, 2002;Harahap & Sagala, 2019;Ibrahim, 2012;O'Boyle Jr, Humphrey, Pollack, Hawver, & Story, 2011;Kirk, Schutte, & Hine, 2011;Krisnanda, Bagus, & Surya, 2019;Mamangkey et al, 2018;Mulyasari, 2018), the nature of emotional intelligence in adolescents (Argyriou, Bakoyannis, & Tantaros, 2016), the effect of emotional intelligence on work practices (Athariq & Andayono, 2019), the effect of emotional intelligence on pro-social behavior (Hanana, 2018;Sahputra & Hayati, 2019), portrait of emotional intelligence in students (Birks, Mckendree, & Watt, 2009;Indriawati, 2018;Luan & Blegur, 2018), the role of emotional intelligence in coping strategies (Felix et al, 2019), the importance of emotional intelligence for leadership (Allameh & Khazaei, 2015;Suryana, 2019), description of emotional intelligence in gifted students (Respati, Arifin, & Ernawati, 2007), consumer emotional intelligence (Kidwell, Hardesty, & Childers, 2008), and the importance of emotional intelligence in learning. From the most recent research, most of the emotional intelligence research applied to the working-age, only a few that examines emotional intelligence in the educational environment.…”
Section: Introductionmentioning
confidence: 99%